2019
DOI: 10.1002/art.40868
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Peroxisome Proliferator–Activated Receptor γ Coactivator 1β/NFATc1 Pathway in Circulating Osteoclast Precursors Associated With Bone Destruction in Rheumatoid Arthritis

Abstract: Objective Activation of osteoclastogenesis at the bone site in rheumatoid arthritis (RA) is well established. The mechanisms by which circulating osteoclast precursors contribute are still unclear. Peroxisome proliferator–activated receptor γ coactivator 1β (PGC‐1β) is implicated in transcriptional regulation of osteoclastogenesis in mouse models. This study was undertaken to investigate the contribution of PGC‐1β to circulating osteoclast precursors and its link to bone destruction in RA. Methods PGC‐1β expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…In addition to inhibiting the differentiation of pro-inflammatory macrophages, PGC-1β can also induce osteoclasts differentiation. PGC-1β is induced during the process of osteoclasts differentiation caused by cyclic adenosine monophosphate (cAMP) ( 114 , 118 ). In vitro or in vivo experiments further demonstrated that down-regulation of PGC-1β inhibits mitochondrial biogenesis and osteoclasts differentiation, and osteoclasts function is severely impaired in PGC-1β-deficient mice ( 114 ).…”
Section: Regulators Of the Differentiation Of Macrophages Into Osteocmentioning
confidence: 99%
“…In addition to inhibiting the differentiation of pro-inflammatory macrophages, PGC-1β can also induce osteoclasts differentiation. PGC-1β is induced during the process of osteoclasts differentiation caused by cyclic adenosine monophosphate (cAMP) ( 114 , 118 ). In vitro or in vivo experiments further demonstrated that down-regulation of PGC-1β inhibits mitochondrial biogenesis and osteoclasts differentiation, and osteoclasts function is severely impaired in PGC-1β-deficient mice ( 114 ).…”
Section: Regulators Of the Differentiation Of Macrophages Into Osteocmentioning
confidence: 99%
“…Results showed that, similar to nitrendipine, both CsA and FK506 treatment effectively blocked the glyburide effect in UCP1 elevation ( Figures 5 C–5F). Moreover, the NFAT inhibitor, VIVIT, which is a cell-permeable peptide inhibitor of nuclear factor of activated T cells (NFAT) that selectively inhibits calcineurin-mediated dephosphorylation of NFAT ( Ma et al., 2019 ), also significantly affected the increase of Ucp1 expression induced by glyburide treatment ( Figure 5 G). Similarly, in white adipocytes, the UCP1 upregulation upon glyburide treatment was also blocked by calcineurin inhibition ( Figure 5 H).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we reported that increased nuclear accumulation of a metabolic transcription factor peroxisome proliferator-activated receptor γ coactivator 1β (PGC1β) in circulating osteoclast precursors from RA patients promoted osteoclastogenesis and was associated with bone destruction. 35 The study of skeletal-muscle-specific PGC1β transgenic mice showed that sustained over-expression of PGC1β promoted apoptosis and autophagy of myofibers by the regulation of mitochondrial biogenesis, and then caused a progressive decrease in muscle mass. 36 The cross-talk between muscle and bone may also be mediated through endocrine cytokines such as myostatin, irisin, and many others, although the relevance of this communication in RA has not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%